2021
DOI: 10.1016/j.conctc.2021.100764
|View full text |Cite
|
Sign up to set email alerts
|

Comparing written exposure therapy to Prolonged Exposure for the treatment of PTSD in a veteran sample: A non-inferiority randomized design

Abstract: Posttraumatic stress disorder (PTSD) is highly prevalent among veterans. Although there are effective treatment approaches for PTSD, such as Prolonged Exposure (PE) and Cognitive Processing Therapy, many providers trained in these approaches do not use them, or use them without sufficient fidelity, and veterans drop out of these treatments at very high rates. The time intensive nature of these treatments is frequently cited as a barrier to receiving the treatment among veterans and delivering the treatment amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…However, future research is needed to examine the effects of adding additional sessions to WET and to ensure flexibility while maintaining the brevity and efficiency that is a potential advantage of this protocol. A current RCT of WET in the VA is examining the frequency with which additional sessions are needed when treating veterans with PTSD (Sloan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, future research is needed to examine the effects of adding additional sessions to WET and to ensure flexibility while maintaining the brevity and efficiency that is a potential advantage of this protocol. A current RCT of WET in the VA is examining the frequency with which additional sessions are needed when treating veterans with PTSD (Sloan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Additional information regarding the therapists and treatment fidelity ratings is described in eMethods 2 in Supplement 2. Detailed information on the study design is reported elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…Because the purpose of the written exposures is to address the trauma memory, writing quality (i.e., grammar, sentence structure, spelling) is unimportant. WET is noninferior to Cognitive Processing Therapy and work is underway on a noninferiority comparison with PE 18,19 . Because of its simplicity and brevity, WET may be more readily implemented in SUD residential care than other exposure‐based approaches for PTSD.…”
Section: Introductionmentioning
confidence: 99%
“…WET is noninferior to Cognitive Processing Therapy and work is underway on a noninferiority comparison with PE. 18,19 Because of its simplicity and brevity, WET may be more readily implemented in SUD residential care than other exposure-based approaches for PTSD. However, to date the only test of WET among people with comorbid SUD is the case study series of group WET, in which only one of the three participants completed treatment.…”
Section: Introductionmentioning
confidence: 99%